2005
DOI: 10.1093/ndt/gfh569
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of glutathione biosynthetic pathway in uraemia and dialysis

Abstract: The activity of the rate-limiting enzyme in GSH biosynthesis, gamma-GCS, was significantly decreased in uraemic and dialysis patients, which explains, at least in part, frequent reports of reduced GSH levels in these patients. The decrease in gamma-GCS activity may have been secondary to inhibitory effects from uraemic factors that are not removed by standard dialysis. However, this assumption does not exclude the possibility of down-regulation of gamma-GCS protein expression and further studies in this contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
2
17
1
1
Order By: Relevance
“…These findings are in accord with many other researchers' findings. [31][32][33] ADMA is one of the most important risk factors for cardiovascular disease. 34 In our study, similar results were obtained as they were in the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accord with many other researchers' findings. [31][32][33] ADMA is one of the most important risk factors for cardiovascular disease. 34 In our study, similar results were obtained as they were in the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…This includes uremia (Alhamdani, 2005), neurodegenerative diseases , and pulmonary fibrosis (Walters et al, 2008). A fall in GCL activity has been reported in some of them.…”
Section: Other Conditionsmentioning
confidence: 99%
“…The data supporting the presence of increased oxidative stress in the progression of CKD are also incomplete. Although studies have shown that the serum levels of glutathione, a vital antioxidant that protects cells against oxidative stress, are reduced in adult uremic patients [4], a direct beneficial role for antioxidant therapy in humans has not yet established. However, Massola Shimizu et al [5] did show that rats subjected to 5/6 nephrectomy who received the antioxidant N-acetylcysteine displayed a greater weight gain, reduced oxidative stress, and higher glomerular filtration rate (GFR) than control rats.…”
Section: Mediators Of Inflammation In Adults With Ckd and End-stage Kmentioning
confidence: 99%